Leisure, Health and Well-Being : A Holistic Approach - Benkő, Zsuzsanna; Modi, Ishwar; Tarkó, Klára (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book explores health and leisure as a holistic phenomenon with individual and social dimensions. Contributors to this edited volume explore the physical, mental, emotional, sexual and social aspects of health and leisure as well as the influence of moral and religious principles. The connections between the individual and the social structure, social integration, the social division of labor, and the natural environment are also analysed. The volume studies this relationship from a range of disciplinary backgrounds, including sociology, psychology, psychiatry, medical sciences, sport sciences, education, policy making, and from both national and international perspectives. As such, the collection will be of interest to scholars and students across a range of disciplines, including Leisure Studies, Health Studies, Health Promotion, Psychology and Mental Health, Sociology and Sport Studies. .
Keywords: Social sciences.; Sports -- Sociological aspects.; Health psychology.; Positive psychology.; elektronické knihy; electronic books